2018
DOI: 10.1021/acs.joc.7b03045
|View full text |Cite
|
Sign up to set email alerts
|

An Acid-Catalyzed Addition and Dehydration Sequence for the Synthesis of Heteroarylated Steroidal Dienes

Abstract: Additions of heteroarenes to hormone steroids containing an α,β-unsaturated ketone are reported. Additions of a range of electron-rich heteroarene nucleophiles, including indoles, a pyrrole, and a thiophene, to a variety of commercially available steroids and subsequent dehydration formed 3-heteroarylated steroidal dienes in up to 93% yield. This atom-economical reaction sequence occurs under mild reaction conditions in the presence of catalytic bismuth triflate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…69,31 Recently, Stanley et al have reported the synthesis of heteroarylated steroidal diene by using bismuth triflate as a catalyst. 32…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…69,31 Recently, Stanley et al have reported the synthesis of heteroarylated steroidal diene by using bismuth triflate as a catalyst. 32…”
mentioning
confidence: 99%
“…[6][7][8][9]31 Recently, Stanley et al have reported the synthesis of heteroarylated steroidal diene by using bismuth triflate as a catalyst. 32 In our pursuit of synthesizing bioactive heterocycles, 33−36 we envisaged the synthesis of thiazolino-androstanedione derivatives via our recently developed methodology that entails a 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) mediated domino reaction of γ-bromo enones (3) with thioamides and thioureas to form thiazoline products (4) under refluxing conditions. 37 Surprisingly, hitherto unknown 3,4-thiazolo-androstenone product (5) was formed instead of the expected 5,6thiazolino-androstenedione derivative (4) (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2531 Novel molecules based on the steroidal core structure are synthesized in a multistep synthesis 7,12,3234 and using catalyst. 29…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole-fused sterone, stanazolol, derivative is known for potent anabolic activities (Figure ). Not surprisingly, syntheses of heterocycle-incorporated steroidal derivatives have been reported in a large number of literature. Novel molecules based on the steroidal core structure are synthesized in a multistep synthesis ,, and using catalyst …”
Section: Introductionmentioning
confidence: 99%